고주파유도 가열에 의한 나노구조의 텅스텐 카바이드 급속소결과 기계적 성질 - 손인진; In Jin Shon; 고인용; In Yong Ko; 홍경태; Kyung Tae Hong; 도정만; Jung Mann Doh; 강현수; Hyun Su Kang (대한금속·재료학회지, 48(11), 2010)
Extremely dense WC with a relative density of up to 99% was obtained within five minutes under a pressure of 80 MPa using the High-Frequency Induction Heated Sintering method. The average grain size of the WC was about 71 nm. The advantage of this process is not only rapid densification to obtain a neartheoretical density but also the prohibition of grain growth in nano-structured materials. The hardness and fracture toughness of the dense WC produced by HFIHS were 2660 kg·mm?2 and 7.2 MPa·m1/2, respectively.